PEMBELAJARAN CONTEXSTUAL TEACHING LEARNING (CTL) MELALUI PEMODELAN MENGGUNAKAN ORGAN TUBUH UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI SISTEM REPRODUKSI MANUSIA - Nurmaliah Nurmaliah (Jurnal Dedikasi Pendidikan, 2020)
National Education, which conducted the government, is determined by school administrators. One of the efforts carried out by the government is upgrading the teacher’s professionalism in the learning-teaching process that can improve student achievement. The learning method, which is presented by the teacher, should be student-centered learning, not teacher-centered. In the concept of CTL, through the model of using organs, the learning outcome is expected to be more useful for the students. One of the CTL learning, which activates students in the study, is modeling. This research aims to know the enhancement of student’s learning outcomes used CTL learning through modeling using human reproductive system material. This research was conducted at third-grade students of MTsN 1 Banda Aceh, with the data were obtained on August 2nd, 2018. The classroom action research (CAR) used two-cycle, where the assessment instrument are learning achievement test questions and observation sheet. The data analysis in the research used descriptive statistics. The result of this research is the average score of student's daily test in class IX-7 at cycle one that does not use modeling 69,63 with completeness 8,33% and incomplete 91,66%. Meanwhile, at cycle two, the average of the daily test used the modeling 82,83 with completeness 88,88% and incomplete 11,11%, where the learning mastery score is 80. This data proved that CTL learning with modeling, which used organs in human reproductive system material, can increase student learning outcomes.